Assessment of UV-VIS spectra analysis methods for quantifying the absorption properties of chromophoric dissolved organic matter (CDOM) - Zeng, Ruosha; Mannaerts, Chris M.; Lievens, Caroline (Frontiers in Environmental Science, 2023)
Several ultraviolet-visible (UV-VIS) spectral analysis methods have been used to quantify the absorption properties of chromophoric or colored dissolved organic matter (CDOM). Different spectroscopic parameters can be used as surrogates of optical properties; furthermore, advanced mathematical tools have also been applied to investigate the absorption spectrum. This study evaluated the most commonly used spectroscopic parameters in remote sensing research and advanced mathematical methods using absorption data on primary biomass constituents (BCs) in aqueous states. We found that, among the eight spectrometric parameters, the spectral slope in the 275-295 nm range (S275–295) had the strongest correlation with the hydrogen to carbon ratio (H/C), the spectral slope ratio (275-295 to 350-400 nm) SR and the absorbance ration between 465 to 665 nm (E4/E6) had strong correlation with oxygen to carbon the ratio (O/C). Additionally, the spectroscopic parameter values for the solutions of the BCs exhibited distinguishable differences. Gaussian fitting was suitable for single CDOM components but not for complex mixtures. Derivative analysis can be used for single-component discrimination with an extensive investigation of the absorption properties of this component. Additionally, we propose a possible bottom-up perspective to track the origins of CDOM through the absorption spectrum.